2021
DOI: 10.1007/s10578-021-01270-y
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Socioeconomic Adversity and Armed Conflict in Executive Function, Theory of Mind and Empathy in Children

Abstract: Acknowledgments: This study was funded by the Patrice L. Engle Dissertation Grant for Global Early Child Development from the Society for Research in Child Development awarded to the first author. We would like to thank the parents and children who participated in the study, and the research assistants who helped with data collection. Conflict of Interest: The authors declare that they have no conflict of interest.This version of the article has been accepted for publication, after peer review but is not the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Finally, several contextual factors have been reported to mediate the ToM-EFs relationship; cultural context (e.g., Chasiotis et al, 2006;Wang et al, 2016), socio-economic status (e.g., Dicataldo & Roch, 2020;Kara & Selcuk, 2021), bilingualism (e.g., Diaz & Farrar, 2018;Sudo & Matsui, 2021), or the "siblings' effect" (McAlister & Peterson, 2006) should be further assessed and carefully controlled for in experimental designs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, several contextual factors have been reported to mediate the ToM-EFs relationship; cultural context (e.g., Chasiotis et al, 2006;Wang et al, 2016), socio-economic status (e.g., Dicataldo & Roch, 2020;Kara & Selcuk, 2021), bilingualism (e.g., Diaz & Farrar, 2018;Sudo & Matsui, 2021), or the "siblings' effect" (McAlister & Peterson, 2006) should be further assessed and carefully controlled for in experimental designs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, FB performance has been associated with other aspects of EFs, such as SH (ages 3-8 years) (Blair & Razza, 2007;Gordon et al, 2014;Guajardo et al, 2009;Kara & Selcuk, 2021;Oh & Lewis, 2008) and planning (PL) (Putko & Zlotogorska, 2014). Furthermore, children's scores (ages 8-11 years) in SH (Cassetta et al, 2018) and PL (ages 3-6 years) (Cole & Mitchell, 2000;Longobardi et al, 2021;Memisevic et al, 2018) have also been found to predict FB performance.…”
Section: Relationship Between Fb and Efsmentioning
confidence: 99%
“…Our research previously showed that armed conflict and poverty were associated with increased levels of violence in the family, which altogether led to higher levels of emotional and behavioral problems in children and adolescents (Kara & Selçuk, 2020) and with lower socio-cognitive skills in early childhood, such as executive functioning and theory of mind (Kara & Selcuk, 2021). However, the cumulative effect of contextual risks and their interaction on youth psychological symptoms has not been studied yet.…”
Section: Psychological Adjustment In the East Of Turkeymentioning
confidence: 97%
“…Executive function abilities stem from fundamental neurobiological maturation that begins early in life and then progresses over a lengthy trajectory of growth and refinement (e.g., Hackman et al, 2015). Variation in SES predicts a broad tenor of academic outcomes (e.g., Best et al, 2011;Lawson & Farah, 2017), basic psychological processes (e.g., Evans et al, 2021;Hackman et al, 2015), language development (Romeo et al, 2022), and social-cognitive competencies (Kara & Selcuk, 2023). However, theoretical models of EF, although widespread in their influence and impact in the field, typically do not consider SES (Miyake et al, 2000;Zelazo & Carlson, 2012).…”
Section: The Impact Of Ses Reporting Patterns On Generalizability Of ...mentioning
confidence: 99%